Hypertrophic cardiomyopathy in a lupus patient: a case of hydroxychloroquine cardiotoxicity. (7th September 2019) - Chang, Amanda; Stolin, Gabriel; Fan, Judith; Larreta, Boris R.; Fishbein, Gregory A.; Wallace, William Dean; Baas, Arnold S.; Cruz, Daniel; Wang, Jessica
Abstract: Hydroxychloroquine (HCQ) is a well‐established and effective immunomodulatory therapy for systemic lupus erythematosus and other autoimmune diseases. While retinal toxicity is a well‐recognized complication, cardiotoxicity is lesser known. This case consists of a 63‐year‐old Filipina on chronic HCQ treatment that led to severe biventricular hypertrophy, increased filling pressure, systemic and pulmonary hypertension, and elevated brain natriuretic peptide. Genetic testing ruled out lysosomal storage disorders but revealed five rare variants of uncertain significance, including one that was temporarily re‐classified as likely pathogenic. Endomyocardial biopsy demonstrated myeloid bodies admixed with curvilinear bodies, most consistent with a diagnosis of HCQ toxicity. This case illustrates the importance of clinical integration of multiple causes of cardiomyopathy, recognition of HCQ cardiotoxicity, and increased uncertainty in genetic test findings among racial minorities.